Pengaruh Sistem Kompensasi Terhadap Produktivitas Kerja Karyawan PT. Pupuk Sriwidjaja (Persero) - Deddi Nifyandi; Muhammad Deni; Tutik Pebrianti; Arubina Bangsawan (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2018)
This research was done in order to investigate the effect of compensation variables which are; salary and benefit, facility and honour toward the productivity of employees at PT. Pupuk Sriwidjaja Palembang, the objectives of this research were: a) to investigate the effect of compensation variables which are; salary and benefit, facility and honour toward the productivity of employees at PT. Pupuk Sriwidjaja Palembang, and b) to investigate which independent variable was dominant in affecting the productivity of employees at PT. Pupuk Sriwidjaja Palembang. The research method used was causal. There were 100 employees used as the relationship between variables was measured by using multiple linear regression analysis. The research findings in general showed that the variables of compensation which are; salary and benefit, facility and honour significantly affected the productivity of employees at PT. Pupuk Sriwidjaja Palembang. Partially, the salary and benefit variable had a dominant factor toward productivity of employees at PT. Pupuk Sriwidjaja Palembang.